Accessibility of prison healthcare for elderly inmates, a qualitative assessment. (November 2017) - Heidari, Raheleh; Wangmo, Tenzin; Galli, Serena; Shaw, David M.; Elger, Bernice S.
Abstract: Aging in custody and the rising population of elderly prisoners are creating compelling challenges for criminal justice, prison and public healthcare systems. Geriatric syndrome and higher prevalence of co-morbidities amongst older inmates result in heightened vulnerability in prison environments. Empirical research addressing older adults' access to medical care in detention is scarce; therefore, this study assessed access to medical care in prison from the perspective of older prisoners in Switzerland. We interviewed a sample of 35 older inmates (average age 61 years) on their experience of healthcare accessibility in prison; data were qualitatively analysed and major themes regarding evaluation of their access to medical services were extracted. Our findings identified three barriers to accessing health services in prison including psychological obstacles, negative consequences of healthcare utilization, and environmental hurdles. We advocate facilitating older inmates' access to medical care in order to relieve the psychological burden of seeking health services in detention and adequately informing them of their right to demand these services, thereby lessening the negative consequences of their requests. We suggest further training of prison and medical staff for better management of age-related issues in prison can ease the environmental obstacles. Highlights: Three categorical barriers restrict the health-seeking behaviour of elderly inmates. Psychological obstacles signify personal reasons to avoid health services in prison. Negative consequences of utilization of healthcare are derived from previous negative experiences and expectations. Environmental hurdles discourage elderly inmates from seeking health services in custody.